Evaluation of the Antihyperglycemic and Antihyperlipidemic Activity of Saussurea hypoleuca Root in Alloxan-Induced Diabetes in Rat Model and Correlation to Its Major Secondary Metabolites - Numera Arshad; Saiqa Ishtiaq; Sairah Hafeez Kamran; Muhammad Sajid-ur Rehman; Shehla Akbar; Saira Rehman; Sarah Rehman; Rawan H. Hareeri; Sana A. Fadil; Fadia S. Youssef; Sameh S. Elhady (Life, 2022)
Saussurea hypoleuca belongs to the family Asteraceae, which has previously shown hepatoprotective, anticancer, and antioxidant activity. This study aimed to evaluate the antihyperglycemic and antihyperlipidemic activity of its root methanol extract and various fractions for the first time. This was performed using alloxan-induced diabetes in the rat model for both short, and long-term periods using different administration doses. Different biochemical parameters were studied and further consolidated by histopathological examination and in silico molecular modeling. The results showed that in the long-term study, at a dose of 400 mg/kg b.wt, the ethyl acetate fraction caused a pronounced reduction in fasting blood glucose level (FBG) and glycated hemoglobin (HbA1c) by 77.2% and 36.8%, respectively, compared to the diabetic group. This was confirmed by the histopathological examination of the animals’ pancreatic sections. The ethyl acetate fraction also showed a reduction in total cholesterol (TC), total glycerides (TG), and low-density lipoprotein cholesterol (LDL-C) levels. It improved kidney and liver functions, causing a reduction in aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine transaminase (ALT), urea, and creatinine levels. This is mainly attributed to its richness in secondary metabolites. Molecular docking showed that all the tested compounds showed certain inhibitory potential towards human α-glucosidase (HAG) and ATP citrate lyase (ACL). Thus, Saussurea hypoleuca roots can help in the management of hyperglycemia, hyperlipidemia, and hepatic and kidney dysfunction.